2022
DOI: 10.3390/ijms231911965
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Paraventricular-Coerulear Network on the Programming of Hypertension by Prenatal Undernutrition

Abstract: A crucial etiological component in fetal programming is early nutrition. Indeed, early undernutrition may cause a chronic increase in blood pressure and cardiovascular diseases, including stroke and heart failure. In this regard, current evidence has sustained several pathological mechanisms involving changes in central and peripheral targets. In the present review, we summarize the neuroendocrine and neuroplastic modifications that underlie maladaptive mechanisms related to chronic hypertension programming af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 159 publications
(243 reference statements)
0
1
0
Order By: Relevance
“…It has also been demonstrated that PVN neurons remain active after long-term glucocorticoid negative feedback ( 51 ), and chronic stress may even increase the excitability of PVN CRH neurons via multiple mechanisms ( 52 ). Our mathematical modeling could also be extended to interrogate other physiological phenomena such as the mechanisms by which the PVN CRH neural system underlies the adverse outcomes of nutritional programming on cardiovascular disease ( 53 ). Another important consideration is the fact that drinking water behavior is not constant throughout the day.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that PVN neurons remain active after long-term glucocorticoid negative feedback ( 51 ), and chronic stress may even increase the excitability of PVN CRH neurons via multiple mechanisms ( 52 ). Our mathematical modeling could also be extended to interrogate other physiological phenomena such as the mechanisms by which the PVN CRH neural system underlies the adverse outcomes of nutritional programming on cardiovascular disease ( 53 ). Another important consideration is the fact that drinking water behavior is not constant throughout the day.…”
Section: Discussionmentioning
confidence: 99%